2015
DOI: 10.1097/btf.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Navicular Body Fractures With a Cerclage Wire Technique

Abstract: This article describes the surgical technique of circumferential cerclage wire used in the treatment of comminuted navicular body fractures. We propose that the use of this percutaneous technique can serve as an alternative means of achieving acceptable reduction and stable fixation while potentially decreasing the complications associated with more invasive open reduction and internal fixation techniques.Level of Evidence: Diagnostic Level 4. See Instructions for Authors for a complete description of levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The literature describes different surgical techniques for the management of these fractures. We wanted to present our experience and describe the use of cerclage as a beneficial hardware to fix navicular fractures; in our cases, the cerclage helped to achieve reduction with lag screws preventing radial displacement of the fragments, as demonstrated in other studies 5,18 . We used a trochanteric cable passer to simplify the technique and make it easily reproducible.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The literature describes different surgical techniques for the management of these fractures. We wanted to present our experience and describe the use of cerclage as a beneficial hardware to fix navicular fractures; in our cases, the cerclage helped to achieve reduction with lag screws preventing radial displacement of the fragments, as demonstrated in other studies 5,18 . We used a trochanteric cable passer to simplify the technique and make it easily reproducible.…”
Section: Discussionmentioning
confidence: 92%
“…If all the fragments were not secured with the cerclage, the reduction was obtained by adding screws to the K-wire to fix the fragments. The postoperative management consisted in 8 weeks of nonweight-bearing, but follow-up was insufficient to describe if and when the hardware was removed 18 . More recently, Sanders et al reported 39 cases of navicular fractures treated based on the fracture pattern using circumferential tension band plates or external fixation to restore the length of the medial column, with K-wires, screws or bridge plates as needed, avoiding arthrodesis whenever possible; this was used only when reconstruction of the articular surfaces was not possible, demonstrating that there is not yet a univocal way to manage these fractures 6 .…”
Section: Discussionmentioning
confidence: 99%